Influence of Mechanical Ventilation Modes on the Efficacy of Nebulized Bronchodilators in the Treatment of Intubated Adult Patients with Obstructive Pulmonary Disease - Cibelle Andrade Lima; Shirley Lima Campos; Monique Pontes Bandeira; Wagner Souza Leite; Daniella Cunha Brandão; Juliana Fernandes; James B. Fink; Armele Dornelas de Andrade (MDPI AG, 2023)
Background: Little has been reported in terms of clinical outcomes to confirm the benefits of nebulized bronchodilators during mechanical ventilation (MV). Electrical Impedance Tomography (EIT) could be a valuable method to elucidate this gap. Objective: The purpose of this study is to evaluate the impact of nebulized bronchodilators during invasive MV with EIT by comparing three ventilation modes on the overall and regional lung ventilation and aeration in critically ill patients with obstructive pulmonary disease. Method: A blind clinical trial in which eligible patients underwent nebulization with salbutamol sulfate (5 mg/1 mL) and ipratropium bromide (0.5 mg/2 mL) in the ventilation mode they were receiving. EIT evaluation was performed before and after the intervention. A joint and stratified analysis into ventilation mode groups was performed, with p < 0.05. Results: Five of nineteen procedures occurred in controlled MV mode, seven in assisted mode and seven in spontaneous mode. In the intra-group analysis, the nebulization increased total ventilation in controlled (p = 0.04 and ⅆ = 2) and spontaneous (p = 0.01 and ⅆ = 1.5) MV modes. There was an increase in the dependent pulmonary region in assisted mode (p = 0.01 and ⅆ = 0.3) and in spontaneous mode (p = 0.02 and ⅆ = 1.6). There was no difference in the intergroup analysis. Conclusions: Nebulized bronchodilators reduce the aeration of non-dependent pulmonary regions and increase overall lung ventilation but there was no difference between the ventilation modes. As a limitation, it is important to note that the muscular effort in PSV and A/C PCV modes influences the impedance variation, and consequently the aeration and ventilation values. Thus, future studies are needed to evaluate this effort as well as the time on ventilator, time in UCI and other variables.